2020
DOI: 10.1101/2020.02.18.20021881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between 2019-nCoV transmission and N95 respirator use

Abstract: 2019-nCoV had caused pneumonia outbreak in Wuhan. Existing evidence have confirmed the human-to-human transmission of 2019-nCoV. We retrospectively collected infection data from 2 January to 22 January at six departments from Zhongnan Hospital of Wuhan University. In our study, we found N95 respirators, disinfection and hand washing can help to reduce the risk of 2019-nCoV infection in

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 3 publications
1
51
0
1
Order By: Relevance
“…Reduces penetration of ultra-fine viral particles 30 No SARS-CoV HCW infections when N95 used in high-risk areas 28 No COVID-19 HCW infections when N95 used 31 CDC recommends N95 for patient contact and aerosol generating procedures 19 Uncomfortable, poorly tolerated by HCWs for >6-7 hours 32 Limited availability Airborne -Elastomeric facepiece respirators (''gas masks'')…”
Section: The Risk To Healthcare Workersmentioning
confidence: 99%
See 3 more Smart Citations
“…Reduces penetration of ultra-fine viral particles 30 No SARS-CoV HCW infections when N95 used in high-risk areas 28 No COVID-19 HCW infections when N95 used 31 CDC recommends N95 for patient contact and aerosol generating procedures 19 Uncomfortable, poorly tolerated by HCWs for >6-7 hours 32 Limited availability Airborne -Elastomeric facepiece respirators (''gas masks'')…”
Section: The Risk To Healthcare Workersmentioning
confidence: 99%
“…23 A study specifically examining critical care nurses also found no differences in the rates of becoming infected when using a surgical mask compared to an N95 mask. 29 Wang et al 31 published healthcare worker infection rates from Wuhan University from December 2019 and showed that none of the 278 staff members who wore N95 masks became infected. Doctors and nurses on surgical floors who did not interact with COVID-19 patients were considered low risk and did not wear masks, and 10 of 215 (4.6%) of these individuals ultimately became infected.…”
Section: Surgical Face Masksmentioning
confidence: 99%
See 2 more Smart Citations
“…N95 respirators (the equivalent in Europe is FFP2 respirators) are recommended for health workers conducting aerosolgenerating procedures during clinical care of COVID-19 patients, while surgical masks are recommended for non-aerosol generating procedures (139). The importance of masks for health worker protection was emphasised in the early phases of the global pandemic in hospitals in China (140). Strategies to manage this critical shortage of PPE have included exploring sterilization and re-use of respirators, and appeals to the public to reduce their use of medical masks.…”
Section: Implementation Considerationsmentioning
confidence: 99%